Does Antenatal Care Translate into Skilled Birth Attendance? Analysis of 2014 Ghana Demographic and Health Survey - Linus Baatiema; Edward Kwabena Ameyaw; Aliu Moomin; Mukaila Mumuni Zankawah; Doris Koramah (Hindawi Limited, 2019)
Background. Despite the high antenatal care attendance rate in Ghana, skilled birth attendance is relatively low. There is limited evidence on whether antenatal care attendance translates into skilled birth attendance in the Ghanaian research discourse. This study investigates whether antenatal care attendance translates into skilled birth. Methods. We extracted data from the 2014 Ghana Demographic and Health Survey. Data were analysed using descriptive and binary logistic regression analyses at 5% confidence interval. Results. The descriptive findings indicated a vast variation between antenatal care attendance and skilled birth attendance. Skilled birth attendance was consistently low across almost all sociodemographic characteristics as compared to antenatal care attendance. The binary logistic regression analysis however indicated higher inclination toward skilled birth attendance among women who had at least four antenatal care visits [OR=5.87, CI=4.86-7.08]. The category of women noted to have higher tendencies of skilled birth attendance was those with higher/tertiary education [OR=9.13, CI=2.19-37.93], the rich [OR=4.27, CI=3.02-6.06], urban residents [OR=2.35, CI=1.88-2.93], women with maximum of four children [OR=1.36, CI=1.08-1.72], and those using modern contraceptives [OR=1.24, CI=1.03-1.50]. Conclusion. We recommend that interventions to enhance skilled birth attendance must target women who do not achieve at least four antenatal visits, those with low wealth standing, those not using contraceptives, and women without formal education. Again, an in-depth qualitative study is envisaged to deepen the understanding of these dynamics in the rural setting.